The gift-giving culture of Anglo-Muscovite diplomacy, 1566-1623 - Zhukova, Tatyana, Alexandra (2018)
In 1589, the government of Tsar Feodor I of Muscovy returned the gift of golden medals received from Queen Elizabeth I, describing the offending objects as neither commendable nor agreeable. The rejection was accompanied with opprobrious public speeches about the gift’s unsuitability and a threat to transfer Muscovite favour unto other European nations if Elizabeth offered no immediate redress. In her defence, Elizabeth argued that diplomatic gifts were to be accepted not in respect of the object itself, but of the royal majesty from whom it was presented. While the episode appears to show a petty squabble over material trinkets, its diplomatic repercussions were significant as the following five years would be dedicated to the repair of Anglo-Muscovite relations. Clearly, gifts were integral to the mechanics of early modern diplomacy.